Language Use Register in the Home-Made Kretek Cigarette Industry Environment in Sampang: Sociolinguistic Study - Vani Indra Pramudianto; Laily Nurlina Iskandar; Sukirno Sukirno (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the use of language registers in the kretek cigarette home industry environment in Sampang Village, Cilacap Regency. Using a qualitative descriptive approach with the method of communication ethnography, this study aims to describe the form, meaning, and socio-cultural function of the typical terms used by workers in cigarette production activities. Data were obtained through direct observation, in-depth interviews, and documentation of linguistic artifacts. The results of the study indicate the existence of a typical vocabulary that reflects social identity, efficiency of work communication, and preservation of local culture. Terms such as klobot, mbako srinthil, tingwek, and ngeses are symbols of the social and cultural structure of the work community. This register not only has a literal meaning but also symbolic and contextual, and functions as an expressive, evaluative, and cultural preservation tool. These findings are relevant in the development of language variation teaching materials and strengthening the profile of students with cultural diversity characteristics.